Basan gets a new fingerprint: Mutations in the skin‐specific isoform of SMARCAD1 cause ectodermal dysplasia syndromes with adermatoglyphia. Issue 11 (5th October 2018) - Valentin, Monica N.; Solomon, Benjamin D.; Richard, Gabriele; Ferreira, Carlos R.; Kirkorian, Anna Yasmine
Abstract : Basan syndrome is an autosomal dominant ectodermal dysplasia (ED) with congenital adermatoglyphia, transient neonatal acral bullae, and congenital facial milia. Autosomal dominant adermatoglyphia (ADG) is characterized as adermatoglyphia with hypohidrosis. Recently mutations in the skin‐specific isoform of the gene SMARCAD1 have been found in both syndromes. This report proposes to unify these two previously distinct ED, into one syndrome. We offer a new acronym: SMARCAD syndrome ( S MARCAD1 ‐associated congenital facialM ilia, A dermatoglyphia, R educed sweating, C ontractures, A cral Bullae, andD ystrophy of nails). Sanger sequencing was performed on genomic DNA from a patient with Basan syndrome using primers designed to flank SMARCAD1 . Sanger sequencing revealed a novel variant, NM_001254949.1:c.‐10 + 2 T > G, in the donor splice site of exon 1 of the skin‐specific isoform. This variant and the other five previously reported variants in Basan syndrome and ADG are all within the same donor splice site. We conclude that Basan syndrome and ADG are on a phenotypic spectrum of a monogenic syndrome which is better described by the acronym SMARCAD syndrome.